Tracking down the Candy Crush Terrorist: the fragile relation between gaming motives and radical attitudes - Greipl, Simon; Lechner, Maximilian; Fischer, Jannik; Schulze, Heidi; Hohner, Julian; Rieger, Diana (Frontiers in Psychology, 2025)
The gaming ecosystem is increasingly observed with the concern that it could pose a threat to public safety, and research accumulates evidence for blatant extremism in the surrounding online space of games. Currently, a connection between gaming and extremism can be established through identity related processes, e.g., gaming-related radicalization elements, distal to gaming itself, such as gaming communities and culture. However, this also raises the question of what the precise function of proximal gaming factors, such as gameplay, mechanics, stories, or game-play motivations, is in the relationship between gaming and extremism. This article aims to shed light on the relation of gaming and extremism by identifying individual profiles of videogame playing based on gameplay motivations and linking them to indications of radical attitudes (here: xenophobia and violence acceptance) as well as conspiracy beliefs that can be associated with extremist beliefs. Further, we include marginalization and anomie as mediators to gain comparative and fine-grained information about the sole impact of gaming motives on radical attitudes. Our findings indicate that while few motivational profiles exhibit weak yet direct connections to radical attitudes, others display the opposite pattern, suggesting a more complex relationship. Marginalization and anomie strongly predict most radical outcome variables and mediate the relationship in most cases, however sometimes negatively. We only found one complex motivational profile that substantially leans toward late-stage radical attitudes, while for instance, dominant social motives clearly inhibit radical outcomes. The current study thus deflates any straightforward perspective on the becoming of a ‘radical gamer'.